2016
DOI: 10.1074/jbc.m116.740266
|View full text |Cite
|
Sign up to set email alerts
|

Endorepellin-evoked Autophagy Contributes to Angiostasis

Abstract: Endorepellin, the C-terminal domain of perlecan, is an angiostatic molecule that acts as a potent inducer of autophagy via its interaction with VEGFR2. In this study, we examined the effect of endorepellin on endothelial cells using atomic force microscopy. Soluble endorepellin caused morphological and biophysical changes such as an increase in cell surface roughness and cell height. Surprisingly, these changes were not accompanied by alterations in the endothelial cell elastic modulus. We discovered that endo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 40 publications
(45 citation statements)
references
References 83 publications
2
43
0
Order By: Relevance
“…It appears that a pattern is emerging in that pro-angiogenic perlecan is anti-autophagic whereas the converse holds true for endorepellin. Intriguingly, recent work in our laboratory [144], has demonstrated that endorepellin and Torin 1, a potent autophagic inducer [145], both inhibit vessel sprouting in an ex vivo model of angiogenesis (Fig. 3F,G), suggesting that autophagy may be one mechanism by which endorepellin inhibits neovascularization.…”
Section: Antithetic Biological Functions Of Perlecan and Endorepellinmentioning
confidence: 87%
See 1 more Smart Citation
“…It appears that a pattern is emerging in that pro-angiogenic perlecan is anti-autophagic whereas the converse holds true for endorepellin. Intriguingly, recent work in our laboratory [144], has demonstrated that endorepellin and Torin 1, a potent autophagic inducer [145], both inhibit vessel sprouting in an ex vivo model of angiogenesis (Fig. 3F,G), suggesting that autophagy may be one mechanism by which endorepellin inhibits neovascularization.…”
Section: Antithetic Biological Functions Of Perlecan and Endorepellinmentioning
confidence: 87%
“…In our study, we discovered that protracted endothelial cell autophagy evoked by endorepellin can curtail neovascularization, as both endorepellin and Torin 1 reduce sprouting in ex vivo aortic ring assays [144]. Notably, the angiostatic activity of endorepellin could be blocked using Compound C, an inhibitor of AMPKα (Fig.…”
Section: Antithetic Biological Functions Of Perlecan and Endorepellinmentioning
confidence: 97%
“…The binding of endorepellin with VEGFR2 is concurrent with its binding to α 2 β 1 integrin and the dual receptor antagonism concur in the inhibition of EC migration and blood vessel maturation [154,155]. More recently, it was also demonstrated that endorepellin evokes autophagy via VEGFR2 signaling contributing to the angiostatic function of the fragment [156,157]. Thus, similarly to what observed with collagens, the cleavage of perlecan gives rise to a fragment displaying an opposite function, which may serve to counterbalance the angiogenic stimulus.…”
Section: Proteoglycans: Complex Functions From the Protein Core Anmentioning
confidence: 99%
“…Peg3 functions downstream of decorin in the induction of autophagy in endothelial cells, and here we provide further evidence that Peg3 also blunts cell migration in both 2D and 3D environments. We must emphasize that Peg3 is positioned in an extracellularly regulated signaling axis where it is a direct downstream target of decorin and endorepellin, two soluble matrix constituents that both halt angiogenesis by interfering with VEGFR2 (5, 9, 10, 109112). Thus, there is a likely possibility of a connection among Peg3, autophagy, and angiogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…We subsequently discovered that Peg3 is essential for decorin-induced autophagy in endothelial cells (5, 6) and that decorin expression is induced both in vitro and in vivo by proautophagic stimuli like starvation and mammalian target of rapamycin (mTOR) inhibition (7, 8). Furthermore, Peg3 is also necessary for the induction of endothelial cell autophagy evoked by another matrix constituent, endorepellin (9, 10), the C-terminal fragment of perlecan previously implicated in angiostasis (1115). Together, these studies show that Peg3 is an important link between soluble matrix molecules and their regulation of a vital cellular process, autophagy (16).…”
Section: Introductionmentioning
confidence: 99%